Microbial dynamics during shelf-life of industrial Ricotta cheese and identification of a Bacillus strain as a cause of a pink discolouration. (August 2016) - Sattin, E.; Andreani, N.A.; Carraro, L.; Fasolato, L.; Balzan, S.; Novelli, E.; Squartini, A.; Telatin, A.; Simionati, B.; Cardazzo, B.
Abstract: Dairy products are perishable and have to be preserved from spoilage during the food chain to achieve the desired shelf-life. Ricotta is a typical Italian soft dairy food produced by heat coagulation of whey proteins and is considered to be a light and healthy product. The shelf-life of Ricotta could be extended, as required by the international food trade market; however, heat resistant microflora causes spoilage and poses issues regarding the safety of the product. Next-generation sequencing (NGS) applied to the Ricotta samples defined the composition of the microbial community in-depth during the shelf-life. The analysis demonstrated the predominance of spore-forming bacteria throughout the shelf-life, mostly belonging to Bacillus, Paenibacillus and Clostridium genera. A strain involved in spoilage and causing a pink discolouration of Ricotta was isolated and characterised as Bacillus mycoides/weihenstephanensis . This is the first report of a food discolouration caused by a toxigenic strain belonging to the Bacillus cereus group that resulted the predominant strain in the community of the defective ricotta. These results suggest that the processing of raw materials to eliminate spores and residual microflora could be essential for improving the quality and the safety of the product and to extend the shelf-life of industrial Ricotta. Highlights: Evaluation of microbial community following the shelf-life of industrial Ricotta from the production to day 60. Next generation sequencing of 16S rRNA gene amplicon libraries using RNA extracted from Ricotta samples as template. Microbiological analysis and community determination of a Ricotta sample presenting pink discolouration. Molecular typing and toxin profile determination of the strain causing pink discolouration.